Hubungan Berat Badan Bayi, Paritas dan Riwayat Preeklampsia dengan Kejadian Perdarahan Postpartum di RSUD Kota Mataram - Vionada, Elin; Mahayani, Ida Ayu Made; Apriliana, Denta Haritsa (Peneliti.net, 2024)
Each birth handle that happens is at hazard of encountering complications amid conveyance, one of which is postpartum hemorrhage (PPH). This think about points to decide the relationship between infant weight, equality and history of preeclampsia with the rate of postpartum hemorrhage in Mataram City Territorial Clinic. The sort of inquire about carried out was expository observational inquire about. Observational inquire about is inquire about that as it were carries out perceptions or perceptions without mediation from the analyst with the point of finding data around why and how the occurrence happened. The comes approximately of the consider showed up a critical relationship between birth weight and the recurrence of postpartum hemorrhage, there was a critical relationship between correspondence and the rate of postpartum hemorrhage, and there was a critical relationship between a history of preeclampsia and the rate of postpartum hemorrhage.